(untitled) (Journal of the College of Basic Education, 2022)
Zinc oxide (ZnO) thin films were grown on glass substrates at 300 using DC magnetron sputtering method. The effects of annealing under various temperatures (350,400) C o for 2 h on the structural properties of ZnO thin films were investigated by X-ray diffractometer. X-ray diffraction analysis revealed that all films have a polycrystalline hexagonal wurtzite crystal structure with the preferentially c-axis oriented normal to the substrate surface. The crystal structure of annealed films did not change considerably, but the peak position(002) and surface grain size increased slightly. The crystallinity levels of the films and other structural parameters were investigated and analyzed.